Enhancing pension adequacy while reducing the fiscal budget and creating essential capital for domestic investments and growth: Analysing the risks and outcomes in the case of Greece - Georgios Symeonidis; Platōn Tēnios; Panos Xenos (Risks, 2021)
Many countries around the world are resorting to mandatory funded components in their multi-pillar pension systems with the purpose of catering for the financial pressure from ageing. This paper aims at analysing the possible replacement rates for such a scheme, by choosing different assumptions and setting the best combined area for the expected result. Then, an approach for analysing the potential for the implementation of such a scheme in Greece is presented along with the actuarially projected expected benefit expenditure and respective accrued capital. A result of the introduction of such a component is expected to be the elevated replacement rate at retirement with a concurrent alleviation of the fiscal burden for the state. The projected scale of savings will also provide domestic financing for investments generating growth.
Keywords: 330; adequacy; capital investment; funded pensions; growth